New Bees of the Genera Andrena and Nomada from the Island Cyprus (Hymenoptera: Apoidea). - Mavromoustakis, George A. (Contributions to Entomology = Beiträge zur Entomologie, 1957)
The author published in this paper the description of three new species of bees from the island Cyprus (Mediterranean East). These bees are Andrena pareklisiae n. sp., Andrena panurgimorpha n. sp., and Nomada polemediana n. sp. Andrena pareklisiae n. sp., and Andrena panurgimorpha n. sp., belong to the subgenus Chlorandrena, the former is related to Andrena luridiloma Strand, from Tsingtau and the latter to Andrena stabiana Morice from Italy. Of these new Cyprian bees Andrena pareklisiae n. sp., is oligotrophic visiting the flowers only of Sinapis alba L., and Alyssum campestre hirsutum M.B., Cruciferae, and Andrena panurgimorpha n. sp., is the host of the parasitic bee Nomada polemediana n. sp. Paratypes from all the new bees mentioned above were placed in Deutsches Entomologisches Institut, Berlin. Nomenclatural Actspanurgimorpha Mavromoustakis, 1957 (Andrena), spec. n.pareklisiae Mavromoustakis, 1957 (Andrena), spec. n.polemediana Mavromoustakis, 1957 (Nomada), spec. n.